Path analysis and ideotypes for plantain breeding - Ortíz, R.; Langie, H. (Wiley, 1997)
Plantains (Musa spp., AAB group) are an important food crop in the humid lowlands of sub-Saharan Africa. Understanding the relationships between growth characteristics and yield potential (t ha-1 yr-1) would be useful in developing an ideotype to guide breeding efforts for this crop. We investigated cause-effect relationships, through path analysis, in yield potential of six plantain landraces (one giant and two medium French; one medium and one giant False Horn; one True Horn) under two production systems (perennial ratooning and replanting after harvest). Each landrace was selected as a random member of a particular type from the plantain gene bank, for a representative sample of the phenotypic diversity of the crop. The plantain landraces were grown for 6 yr in a split-plot randomized complete block design, with four replications of 30 competing plants per subplot. Landrace was the main plot and production system was the subplot. There were few common pathways determining yield potential among the plantain landraces, so we could not define a common ideotype for plantain breeding. This suggests that plantains may possess different genes controlling similar pathways, or different traits contributing to yield potential. Also, the defined ideotypes differed for each landrace, according to the production system. Plantain breeders should consider those relationships that are affected by both genotype and production system when selecting for improved hybrid germplasm.